Assessment of knowledge, attitude and practice towards e-learning among undergraduate medical students, Andhra Medical College, Visakhapatnam - Vadlamani, Sarada; Kandipudi, Lakshmi Prasad; Bhimarisetty, Devi Madhavi (International Journal Of Community Medicine And Public Health, 2019)
Background: E-learning refers to utilization of internet technologies to enhance knowledge and performance of the learners and to improve the effectiveness of educational interventions. From the review of literature it was evident that e-learning has gained popularity in past decade, however its use is variable among medical colleges. The objectives of the present study were to assess knowledge, attitude and practice towards e-learning among undergraduate medical students. Methods: A cross-sectional study was done among 150 medical students (50 each from 1st, 2nd and 3rd year) of Andhra Medical College, Visakhapatnam in the Month of December 2018. A pre-tested semi-structured questionnaire was administered to access the knowledge and practices. Students’ responses in attitude were collected and rated on 5-point Likert scale from 1=strongly disagree to 5=strongly agree. Results are displayed in frequencies and proportions. A p value of <0.05 is considered as statistically significant. Results: A total of 150 undergraduate medical students were included, among them 67 (40.6%) were males, 98 (59.4%) were females. Majority were aware of e-learning. Nearly 46.7% students used both laptop and smart phones for purpose of e-learning. About 53% were confident in using software applications. Most of students agreed that e-learning has important role in acquiring clinical skill along with other learning methods and 88% of students agreed that it should be supplemented in regular teaching curriculum. The 3rd year students were found to have better attitude towards e-learning than other students. Conclusions: Majority felt that e-learning plays an important role in acquiring clinical skill along with other learning methods in educational institute. So, there is need to provide necessary infrastructure and include e -learning as a part of curriculum in medical education.